Factors influencing luteal angiogenesis and alternative splicing in the bovine ovary - Thompson, Robert F. (2018)
The fertility of the cow is influenced by a variety of factors. Two factors of particular importance are the growth and development of corpus luteum (CL) and the impact of diet. Angiogenesis is integral to luteal development, and is critically regulated by the balance of pro- and anti-angiogenic factors. However, the role of many anti-angiogenic factors in the bovine CL has not been investigated. Therefore, the first aim of this study was to identify the spatial and temporal expression of VEGFA, VEGFA164b and PEDF in the bovine CL, and to determine the effect of PEDF and THBS1 on early luteal angiogenesis and steroidogenesis in vitro. Immunohistochemistry and Western blotting demonstrated that PEDF and VEGFA were expressed at all stages of luteal development, with PEDF concentration greatest in the early CL. In contrast, evidence of luteal VEGFA164b expression was limited. Luteal angiogenesis cultures were subsequently treated with PEDF (0, 10 and 100ng/ml; n=3) or THBS1 (0, 100, 1000ng/ml; n=3) for 5 days. Image analysis of von Willebrand factor immunohistochemistry was performed to quantify the effect on endothelial cell (EC) growth parameters. PEDF (10ng/ml) markedly reduced total and average EC area (P<0.05), total branch length and number of branch points, as well as the degree of branching within each EC cluster (P<0.05). A preliminary study showed that 1000ng/ml THBS1 reduced the degree of branching per EC cluster (P=0.03), but not other parameters. In further studies, THBS1 treatment had no effect on any EC network parameter. In addition, neither treatment had any effect on progesterone production. Adequate dietary protein is essential for growth, however the effect of a high level of dietary protein on the bovine ovary has not been established. The second aim of this study was to determine the effect of a high protein diet on alternative splicing of the granulosa cell transcriptome, and to predict the effects of alternative splicing on the genes and gene ontologies controlling granulosa cell function in silico. Beef heifers were fed either control (11%) or high (14%) crude protein diets for at least 60 days. Granulosa cells were collected from multiple medium-sized follicles at slaughter and pooled by diet. Alternative splicing events were identified following rMATs analysis of RNAseq transcription data obtained from the granulosa cells of medium sized follicles from beef heifers fed a control (n=2) or high protein diet (n=1). 127 genes were found to be commonly spliced across analyses of the two controls vs. one high protein comparisons, with 5 genes undergoing two types of splicing simultaneously. Multiple patterns of splicing were observed and the most common type was skipped exon splicing. Gene ontology analysis showed that the high protein diet altered the splicing of genes involved in the regulation of the cell cycle and mitosis. Functional analysis with GeneMANIA showed that angiogenic factors including FLT1, VEGFA and NRP1 were linked to several of the spliced genes by shared domains, and physical or genetic interactions. BCAS3, PGF, IRF1 and HPSE were identified as genes of interest, splicing caused the insertion of a premature stop codon in PGF, HPSE and IRF1 sequences and thus is predicted to alter function. In conclusion, this study has shown that anti-angiogenic factors are expressed by the early corpus luteum and have the potential to dramatically inhibit luteal angiogenesis. In addition, ovarian function may also be regulated by dietary protein, whereby the degree and pattern of alternative splicing is predicted to influence critical processes including angiogenesis, cell division and mitosis.